Relations between particle size of HDL and LDL lipoproteins and cholesterol esterification rate - Dobiásová, M; Urbanová, Z; Samánek, M (Physiological research, 2005)
Particle size of low density (LDL) and high density (HDL) lipoproteins and cholesterol esterification rate in HDL plasma (FER(HDL)) are important independent predictors of coronary artery diseases (CAD). In this study we assessed the interrelations between these indicators and routinely examined plasma lipid parameters and plasma glucose concentrations. In 141 men, healthy volunteers, we examined plasma total cholesterol (TC), triglycerides (TG), HDL and LDL cholesterol (HDL-C, LDL-C) and HDL unesterified cholesterol (HDL-UC). Particle size distribution in HDL and LDL was assessed by gradient gel electrophoresis and FER(HDL) was estimated by radioassay. An effect of particle size and FER(HDL) on atherogenic indexes as the Log(TG/HDL-C) and TC/HDL-C was evaluated. Subjects in the study had plasma concentrations (mean +/- S.D.) of TC 5.2+/-0.9 mmol/l, HDL-C 1.2+/-0.3 mmol/l, TG 2.1+/-1.7 mmol/l, glucose 5+/-0.8 mmol/l. Relative concentration of HDL(2b) was 17.6+/-11.5 % and 14.6+/-11.8 % of HDL(3b,c). The mean diameter of LDL particles was 25.8+/-1.5 nm. The increase in FER(HDL) significantly correlated with the decrease in HDL(2b) and LDL particle size (r = -0.537 and -0.583, respectively, P<0.01) and the increase in HDL(3b,c) (0.473, P<0.01). Strong interrelations among TG and HDL-C or HDL-UC and FER(HDL) and particle size were found, but TC or LDL-C did not have such an effect. Atherogenic indexes Log(TG/HDL-C) and TC/HDL-C correlated with FER(HDL) (0.827 and 0.750, respectively, P<0.0001) and with HDL and LDL particle size.
Keywords: Humans; lidé středního věku; Lipoproteins, HDL; Aged; dospělí; senioři; lidé; lipoproteiny HDL; velikost částic; Regression Analysis; Adult; lipoproteiny LDL; Male; Middle Aged; estery cholesterolu; Cholesterol Esters; Lipoproteins, LDL; mužské pohlaví; Particle Size; regresní analýza